2012
DOI: 10.1371/journal.pone.0043435
|View full text |Cite
|
Sign up to set email alerts
|

miRNA Regulation of Gene Expression: A Predictive Bioinformatics Analysis in the Postnatally Developing Monkey Hippocampus

Abstract: Regulation of gene expression in the postnatally developing hippocampus might contribute to the emergence of selective memory function. However, the mechanisms that underlie the co-regulation of expression of hundreds of genes in different cell types at specific ages in distinct hippocampal regions have yet to be elucidated. By performing genome-wide microarray analyses of gene expression in distinct regions of the monkey hippocampal formation during early postnatal development, we identified one particular gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…When one gene was represented by more than one probeset, we only considered the probeset exhibiting the largest change. As described in a previous study, 23 some genes may be represented by different probesets exhibiting opposite patterns of expression; with an upregulated pattern that might represent the expression of microRNA targeting that gene, rather than mRNA. We therefore eliminated the probeset susceptible to represent microRNA expression.…”
Section: Methodsmentioning
confidence: 68%
See 1 more Smart Citation
“…When one gene was represented by more than one probeset, we only considered the probeset exhibiting the largest change. As described in a previous study, 23 some genes may be represented by different probesets exhibiting opposite patterns of expression; with an upregulated pattern that might represent the expression of microRNA targeting that gene, rather than mRNA. We therefore eliminated the probeset susceptible to represent microRNA expression.…”
Section: Methodsmentioning
confidence: 68%
“…These animals were the same used in previous studies. 22, 23 We refer the reader to these publications for detailed descriptions of RNA sample acquisition and microarray analyses using the GeneChip Human Genome U133 Plus 2.0 (Affymetrix, Santa Clara, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Because miRNA generally bind multiple mature mRNA species it has been predicted that they might be important for co-ordinated control of gene expression in multiple species (Favre, Banta Lavenex, & Lavenex, 2012). It has been suggested that miRNA:mRNA interactions are particularly important in allowing for maintaining the overall stability in gene expression levels while still allowing for fine-tuning in response to developmental stimuli (Follert, Cremer, & Béclin, 2014).…”
Section: Non-coding Rnamentioning
confidence: 99%
“…Indeed, it is now well established that the hippocampal formation is not a single structure, but comprises a number of distinct regions and circuits Lavenex & Amaral, 2000) that subserve different computational processes and memory functions (Copara et al, 2014;Kesner, Lee, & Gilbert, 2004;Nakashiba et al, 2012). Our recent work at the genetic and neuroanatomical levels revealed that different hippocampal regions mature at different times during development (Favre, Banta Lavenex, & Lavenex, 2012a, 2012bJabès, Banta Lavenex, Amaral, & Lavenex, 2010Lavenex, Banta Lavenex, & Amaral, 2007;Lavenex, Sugden, Davis, Gregg, & Banta Lavenex, 2011). These findings, together with our studies of the development of human spatial memory (Ribordy, Jabès, Banta Lavenex, & Lavenex, 2013;Ribordy Lambert, Lavenex & Banta Lavenex, 2015), support the hypothesis that the differential maturation of distinct hippocampal circuits might underlie the differential emergence of specific ''hippocampus-dependent'' memory processes, culminating in the emergence of adult-like episodic memory concomitant with the maturation of all hippocampal circuits .…”
Section: Hippocampusmentioning
confidence: 99%